HISTORY OF THE DEVELOPMENT OF NEUROSURGERY AS A SPECIALTY - Kadyrbergenov Ruslan (Modern American Journals, 2026)
The purpose of this message is to demonstrate the features of the formation of neurosurgery as an independent clinical discipline in various countries of Europe (USSR, Great Britain, France, Germany) and North America (USA, Canada) using a systematic approach. Considering neurosurgery as a system, we created a doctrine of system-forming factors, called in this case discipline-forming factors. There are three of these factors: 1) socio-historical; 2) natural science; 3) institutional. The socio-economic factor includes wars and the level of development of society; natural science - the successes of natural science that made possible the emergence of modern surgery. At the same time, neurosurgery itself was an experimental testing ground for testing physiological concepts and establishing the role of certain brain structures in health and disease. The components of the natural science factor are: the creation of special diagnostic methods, surgical instruments, the development of new surgical approaches. The institutional factor provides for the emergence of leaders with their own style of clinical and scientific activity, their creation of surgical schools, personnel training systems, organization of specialized departments, departments and institutes, professional societies and journals. Thus, neurosurgery as a specialty with its own philosophy, methods, instruments and area of scientific interests was formed in the interwar period (1920-1930s of the twentieth century). Created on the basis of a systematic approach to the genesis of neurosurgery, the doctrine of discipline-forming factors can contribute to the analysis of the formation and development of other medical disciplines both in the global and national context.
Keywords: History of the development of neurosurgery, specialization in medicine, medicine of the twentieth century.